Latinamerican Community Social Psychology as Critical Social Psychology - Jiménez-Domínguez, Bernardo (Revista de Psicología, 2004)
The process of development of community social psychology is described. This process coincides with a criticism of the medical model, as well the insufficiency of the psychiatric and psychotherapeutic solutions to psychological problems in the framework of a restatement of the relevance of the Social Sciences in the understanding of Latin-American reality and the commitment with a solution of these problems. This happens simultaneously with the crisis of mainstream social psychology. The answer to such a crisis is a psychology reinserted in the field of social sciences and the qualitative, critical and forgotten perspectives denied by mainstream psychology. From these developments relationships with the international emergence of a critical social psychology are established Community social psychology of Latin America is considered a main contribution in this perspective.